Economic development for Africa south of the Sahara: proceedings of a conference held by the International Economic Association - Robinson, E. A. G.; International Economic Association (New York: St Martin's Press, 1964)
This volume is the proceedings of the third regional conference of the International Economic Association, held in Addis Ababa in 1961, was concerned mainly with the practical problems of planning economic development in African countries and growth theory. The collection of papers include: discussions on Africa's present economic situation and potential; and criticism of theories of economic growth in their African application.
Bibliographical footnotes.
lje 28/09/2018
Loans
Keywords: Economic development; Economic growth; Africa, Sub-Saharan